Studi Akses Makanan Bergizi Keluarga dengan Balita Stunting Pada Sistem Penanggulangan Stunting di Lumajang, Indonesia : Studi Akses Makanan Bergizi Keluarga dengan Balita Stunting pada Sistem Penanggulangan Stunting di Lumajang, Indonesia - Dewi Rokhmah; Farianingsih; Isa Ma’rufi; Khoiron (Universitas Airlangga, 2022)
Background: The ability to access food according to needs is influenced by educational and knowledge factors, socio-cultural, geography, and economic factors. Overcoming stunting not only overcomes the problem of malnutrition but also must pay attention to the problem of affordability or access to nutritious food Objectives: To analyze access to nutritious food in the prevention system stunting in Lumajang Regency Methods: Qualitative research through a Case Study approach conducted in two villages in Lumajang Regency. The research informants consisted of key informants namely the Head of the Puskesmas, the main informants were mother with toddler Stunting and additional informants namely stakeholders related to stunting. Data processing and analysis using the Thematic Content Analysis method. Results: Access to nutritious food that is less than optimal is caused by economic factors that are lacking, lack of knowledge of mothers of toddlers, malnutrition in toddlers, children's eating arrangements are not meeting nutritional adequacy, children's consumption in a day is lacking, families do not take action to overcome children's nutritional problems and poor sanitation and environmental health Conclusions: Stunting in Lumajang Regency is the cause of which is access to nutritious food that is less than optimal so that it requires attention and cooperation from all parties to overcome it. The provision of education in the form of counseling needs to be carried out with multimethods and multi-media as well as integrated countermeasurements from all existing resources will accelerate the reduction of stunting cases in Lumajang Regency.